Synthesis, Characterization And Catalytic Performance Of Cu/Zno/Sba-15 For Hydrogenation Of Carbon Dioxide To Methanol - Mohamed Razali, Nurul Aini (2014)
Carbon dioxide (co2) is the primary greenhouse gas that causes global warming. The conversion of co2 into methanol (ch3oh) is an alternative to the costly geological and oceanic co2 sequestration. Ch3oh is an important feedstock in the chemical industries and known as an alternative fuel. The catalytic co2 conversion and ch3oh space time yield (sty) is however reported to be considerably low. It is therefore of importance to develop novel catalysts with improved properties for catalytic growth. Santa barbara amorphous 15 (sba-15) with highly ordered hexagonal structure, uniform pore diameter (—5.5 nm) and particle morphology, thicker wall-thickness (3.0 to 5.0 nm), high surface area (585.20 m2/g) and high thermal stability was successfully synthesized by the conventional method without hydrothermal aging process. The synthesized sba-15 was used as catalyst support. A number of monometallic and bimetallic catalyst of copper (cu) or/and zinc oxide (zno) supported on sba-15 were synthesized by simple reflux method. The physicochemical properties of the as-prepared catalysts were investigated by x-ray diffraction (xrd), nitrogen adsorption,